Research progress of immune checkpoint inhibitors in ovarian cancer - Lingli Zhao; Yanhong Zhai; Gaoli Niu (Exploration of Immunology)
Ovarian cancer is the deadliest malignant tumor in the female reproductive system. Despite advancements in standard treatments such as tumor debulking surgery and platinum-based chemotherapy, the overall survival rate remains low. The emergence of targeted therapies, including Poly(ADP-ribose) polymerase (PARP) inhibitors and anti-angiogenic agents, has provided new avenues for treatment. However, drug resistance and disease heterogeneity continue to pose significant challenges. Immune checkpoint inhibitors (ICIs), as an emerging therapeutic approach, primarily target the programmed cell death protein 1 (PD-1)/programmed cell death ligand 1 (PD-L1) and cytotoxic T-lymphocyte antigen 4 (CTLA-4) pathways to restore anti-tumor immune responses. Although ICIs have shown significant efficacy in other malignancies, their effectiveness in ovarian cancer is limited, with a response rate of only 10–15% for monotherapy. Recent studies have focused on combining ICIs with chemotherapy, anti-angiogenic agents, or PARP inhibitors to enhance therapeutic outcomes. This article reviews the progress of ICIs in ovarian cancer, including monotherapy and combination treatment strategies, and explores emerging therapeutic targets and strategies aimed at improving patient prognosis and achieving personalized treatment. By gaining a deeper understanding of the tumor microenvironment and its immune evasion mechanisms, there is hope for developing more effective treatment options in the future, ultimately improving the survival rates and quality of life for ovarian cancer patients.